Rumination and Performance in Dynamic, Team Sport - Roy, Michael M.; Memmert, Daniel; Frees, Anastasia; Radzevick, Joseph; Pretz, Jean; Noël, Benjamin (Frontiers in Psychology, 2016)
People high in rumination are good at tasks that require persistence whereas people low in rumination are good at tasks that require flexibility. Here we examine real world implications of these differences in dynamic, team sport. In two studies, we found that professional male football (soccer) players from Germany and female field hockey players on the US national team were lower in rumination than were non-athletes. Further, low levels of rumination were associated with a longer career at a higher level in football players. Results indicate that athletes in dynamic, team sport might benefit from the flexibility associated with being low in rumination.